DEVELOPING A TEXTBOOK WITH BIG BOOK MEDIA BASED BASAL READERS METHOD TO IMPROVE EARLY READING AT LOW CLASSES - Yani Agustiningrum; Slamet Utomo; Irfai Fathurrohman (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to develop a basal readers method with Big Book media for educators and first grade students which was valid, practical, and effective. The development process was carried out based on Borg & Gill model which emphasized the context of needs (educators and students) so that a textbook for early reading skills could be produced through Big Book media based Basal Readers method. The results of the validity test, which was obtained from the validation of content, language, presentation, graphics, found that the total percentage was 93.10% with Very Valid category. Then, the results of the questionnaire revealed that the percentage of the teacher's response was 90.25% and for the students’ responses was 87.22% while the effectiveness of early reading based on the t-test showed that the value of t count > t table = 5.458 > 2.414. It was concluded that the textbook with big book media based basal readers method was feasible to be used in early reading at the lower grades of elementary school.